2005
DOI: 10.1002/masy.200551410
|View full text |Cite
|
Sign up to set email alerts
|

Xylans from Oat Spelts and Birch Kraft Pulp

Abstract: Two different approaches for the isolation of xylan from hemicelluloserich sources have been investigated: Alkaline extraction from roller-mill pretreated oat spelts and Nitren extraction of birch kraft pulp. For xylan recovery from oat spelts the experiments included extraction with 5% NaOH at 90 8C, followed by precipitation in methanol or 2-propanol without neutralisation in order to facilitate NaOH recovery. A subsequent peroxide bleaching yielded a product of approximately 90% ISO brightness. The work on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…However, residues from agriculture represent a low cost source of xylan containing material that could be turned into an industrial opportunity if it is processed into value adding products (cf. van Wyk 2001;Puls et al 2006), where barley husks have been shown great potential (Glasser et al 2000;Höije et al 2005). The structure of barley husk xylan was early identified (Aspinall and Ferrier 1957) and is now fully characterized by means of NMR (Höije et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, residues from agriculture represent a low cost source of xylan containing material that could be turned into an industrial opportunity if it is processed into value adding products (cf. van Wyk 2001;Puls et al 2006), where barley husks have been shown great potential (Glasser et al 2000;Höije et al 2005). The structure of barley husk xylan was early identified (Aspinall and Ferrier 1957) and is now fully characterized by means of NMR (Höije et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The differences in the pattern of degradation products from the two xylans likely reflect the known differences in the structures of these xylans (13,17). Oat spelt xylan consists of arabinoxylan with trace glucose substituents, while birchwood xylan is primarily an unsubstituted xylose polymer with traces of uronic acids as side groups (17,22,30).…”
mentioning
confidence: 99%
“…[1][2][3][4] To get information about the reactivity of different xylans, the carboxymethylation under comparable conditions was investigated. Table 1 shows the results of the heterogeneous reaction and the carboxymethylation starting with the dissolved polymer of xylans from different sources.…”
Section: Carboxymethylation Of Different Xylan Typesmentioning
confidence: 99%
“…Mostly the completely heterogeneous conversion yields higher DS values. Figure 6 shows 1 H NMR spectra of CMX of different xylans after chain degradation with 25% D 2 SO 4 . The signals for the protons of the CM substituents in position 2 and 3 can be identified.…”
Section: Carboxymethylation Of Different Xylan Typesmentioning
confidence: 99%
See 1 more Smart Citation